Komoditas Unggulan dan Daya Saing Sektor Pertanian di Kabupaten Sijunjung Provinsi Sumatera Barat - Pebry Aldy Saputra; Syahrial Syahrial; Alvindo Dermawan (Jurnal Ekonomi, 2022)
The agricultural sector is the main driver of the increase in regional gross regional product. This study aims to examine the pattern of economic development in the agricultural sector of Sijunjung Regency. In Sijunjung Regency, West Sumatra Province, this research was conducted. Entropy Diversity Index and Klassen Typology are analytical techniques used. The results of the analysis show that the agricultural sector of Sijunjung Regency has not yet developed. Lowland rice, mango, durian and banana commodities are rapidly growing commodities that dominate the agricultural economic growth of Sijunjung Regency.